ENHANCING BUSINESS PERFORMANCE OF CV. JATI MAKMUR PASURUAN USING E-BROCHURE MARKETING STRATEGY - Muhammad Dawilah; Putu Soviyanti; Haila Alzamel; Chin Na a/p Bun Tien; Kemas Ichwan Jaya Satria (International Journal of Applied Business and International Management, 2017)
This report provides an analysis and evaluation of CV Jati Makmur in entering the new market. CV. Jati Makmur is a plywood industry operating more than 15 years in producing woodworking, aiming to grasp the international market for expansion. There are various analysis methods included in the observation. These methods of analysis include Segmenting, Targeting, and Positioning. To conquer the market share in China and Japan as well to increase economic competitiveness several recommended strategies in incorporated. This strategy involves pricing strategy distribution and promotion strategy. In addition, this report also observes the fact that the analysis contains some limitations as well as risks. These risks include external factors such as Government, Competition, and Technology that will affect the future development of CV. Jati Makmur. This report finds the prospects for CV. Jati Makmur in its current position is positive. The major area of weakness requires further investigation and remedial action by management.